Immunomodulatory Effects of Vitamin D in Influenza Infection - Rezaei, Ramazan; Aslani, Saeed; Marashi, Mahdi; Rezaei, Farhad; Sharif-Paghaleh, Ehsan (Current Immunology Reviews (Discontinued), 2018)
Background: Vitamin D has mainly been described in the literature beyond its skeletal functions, including an influence on the immune responses against infections. Observational and interventional studies have represented evidence that Vitamin D deficiency may cause increased risk of seasonal influenza and pulmonary tract infection. Methods: A structured search of EMBASE, Medline, and Web of Science databases was fulfilled to extract all eligible articles published prior to September 2017. Results: In this review, our goal is to define the possible mechanisms that link influenza-mediated immune responses to Vitamin D. Herein, we first briefly describe the role of Vitamin D in the immune responses and then elucidate three immunological processes that connect Vitamin D to influenza infection. Finally, we describe randomized controlled trials and observational studies exploring the effect of Vitamin D supplementation on seasonal influenza infections and vaccinations. Conclusion: Our literature review suggests that treatment of influenza-infected individuals with Vitamin D supplements or cathelicidin-derived agents may provide appreciable protection against natural influenza infection. Moreover, Vitamin D given at appropriate doses may facilitate protection against seasonal flu.
Keywords: infection